2016
DOI: 10.1152/jn.01037.2015
|View full text |Cite
|
Sign up to set email alerts
|

Temporal correlations among functionally specialized striatal neural ensembles in reward-conditioned mice

Abstract: Bakhurin KI, Mac V, Golshani P, Masmanidis SC. Temporal correlations among functionally specialized striatal neural ensembles in reward-conditioned mice. J Neurophysiol 115: 1521-1532, 2016. First published January 13, 2016; doi:10.1152/jn.01037.2015.-As the major input to the basal ganglia, the striatum is innervated by a wide range of other areas. Overlapping input from these regions is speculated to influence temporal correlations among striatal ensembles. However, the network dynamics among behaviorally re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 87 publications
7
56
0
Order By: Relevance
“…The neural clusters identified in this manuscript may contribute to the formation of the cell assemblies identified in previous studies (Adler et al, 2012; Bakhurin et al, 2016; Carrillo-Reid et al, 2008; Jaidar et al, 2010; Ponzi and Wickens, 2012). Computation modeling of striatal networks (Ponzi and Wickens, 2012) has predicted that a real striatal network at its characteristic sparse connectivity level should display a connectivity distribution following the power-law distribution that were scale-free and capable of self-organizing (Barabasi and Albert, 1999).…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…The neural clusters identified in this manuscript may contribute to the formation of the cell assemblies identified in previous studies (Adler et al, 2012; Bakhurin et al, 2016; Carrillo-Reid et al, 2008; Jaidar et al, 2010; Ponzi and Wickens, 2012). Computation modeling of striatal networks (Ponzi and Wickens, 2012) has predicted that a real striatal network at its characteristic sparse connectivity level should display a connectivity distribution following the power-law distribution that were scale-free and capable of self-organizing (Barabasi and Albert, 1999).…”
Section: Discussionsupporting
confidence: 57%
“…Previous studies employing neural clustering approach identified cell assemblies that represented functional states of the striatal network (Adler et al, 2012; Bakhurin et al, 2016; Carrillo-Reid et al, 2008; Jaidar et al, 2010; Ponzi and Wickens, 2012). We therefore applied similar neural clustering approach (Humphries, 2011; Ozden et al, 2008) to our data and identified neural clusters of D1- or D2- MSN based solely on their calcium activity correlation (Figure S4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, with the exception of the separation into patch and matrix compartments, there is no anatomical evidence for spatial organization in the striatum. Nevertheless, SPNs are active in dynamically-organized, competing functional assemblies (Bakhurin et al, 2016; Redgrave et al, 2011), suggesting the existence of microcircuits that underlie such spatial ensembles.…”
Section: Introductionmentioning
confidence: 99%